Interaction between gadolinia-doped ceria electrolyte and sealing glass–ceramics. Issue 7 (July 2015) - Fang, Lihua; Zhang, Qi; Lin, Fen; Tang, Dian; Zhang, Teng
Abstract The insufficient thermal–mechanical stability of sealing interface presents a challenge for the development of solid oxide fuel cells (SOFCs). Here we report for the first time that the presence of gadolinia-doped ceria (GDC) electrolyte leads to the formation of two hardystonite phases, (Ca0.9Zn0.03)2(Al0.63Zn0.37)(Si0.69Al0.31)2O7 and Ca2ZnSi2O7, in the reaction couples between boroaluminosilicate sealing glass–ceramics and GDC powders held at 700 °C for 30 days. Similarly, the aggregation of these two hardystonite phases also occurs at the interface between GDC and sealing glass–ceramics under identical heat-treatment. In particular, (Ca0.9Zn0.03)2(Al0.63Zn0.37)(Si0.69Al0.31)2O7 becomes the dominant phase at the sealing interface when the heat-treatment time increases from 7 days to 30 days. Moreover, the sealing interface remains intact after thermal cycles for 100 times, indicating the excellent thermal–mechanical stability of hardystonite phases. Finally, the possible mechanism on the phase evolution of glass–ceramic at the sealing interface has been proposed.